SISTEM INFORMASI KNOWLEDGE MANAGEMENT PADA PERGURUAN TINGGI STMIK WIDYA DHARMA PONTIANAK - Saragih, Hoga; Darmanto, Tony; Reza, Bobby; Setiyadi, Didik (Teknik dan Ilmu Komputer, 2012)
Knowledge sharing is one of important issues in a company because it is a required approach to facilitate knowledge recording and to improve the effectiveness of knowledge sharing among colleagues. Knowledge sharing accelarates the knowledge transfer. The application of knowledge sharing with the web based system is expected to be a solution for meeting the organizationâs needs. The absence of policy and culture among the lecturers to carry out web based knowledge management results in knowledge sharing difficulties among the students and the faculty members in the long run. This research analyzes the web based knowledge management approach to accelerate the teaching and learning process quality at the STMIK Widya Dharma.Â Â Â Keywords: knowledge, knowledge management, knowledge sharing, knowledge transfer, web design, knowledge management application, UML